Classification of births according to Robson 10 group classification: an emerging concept to audit the increasing caesarean section rate - Kolusu, Priyanka; Himabindu, Palutla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: High caesarean birth rates are an issue of international public health concern. Worries over such increases have led the WHO to advice that caesarean section rate should not be more than 15%. WHO proposes that the health care facilities to use the Robson’s 10 group classification system to audit their CS rates. Our aim was to investigate the CS rates in a period of 6 months using Robso’s 10 group classification. Methods: This was a cross sectional study conducted for a period of 6 months from July 2018 to December 2018 in Department of Obstetrics and Gynecology, Siddhartha medical college which is a tertiary care center .All women delivered during this period in labour ward were included. All relevant obstetric information (parity, mode of previous deliveries, previous CS and indications, gestational age, onset of labor) was entered on a questionnaire and classified into Robson’s 10 classes and percentages were calculated. Results: Total number of deliveries in 6 months is 4719 out of which C-sections are 1816 which accounts for 38.48%. Highest contribution was by group 5 and group 2. Together these two groups contribute to 62.4% of the total caesarean sections. Group 6 and group 9 by themselves did not contribute much but within their groups had 100% C-section rates. Conclusions: Robson’s 10 group classification provides easy way in collecting information about caesarean section rate which obtains good insight into certain birth groups. Number of women who attempt VBAC has declined over recent years due to fear of uterine rupture. Reducing primary C-section rates, adequate counseling and changing norms for non-reassuring fetal status could reduce contribution of Robson’s groups towards absolute C-section rates.